Individual responses to purple grape juice consumption on endurance, explosive power, and fatigue in young male elite soccer players - Niknam, Alireza; Tahmasebi, Kamran; Hemmatinafar, Mohammad; Alkasasbeh, Walaa Jumah; Willems, Mark E. T.; Jahromi, Maryam Koushkie; Kalayeh, Morteza Bagheri; Zare, Mohammad Hadi (Frontiers in Nutrition, 2025)
BackgroundPurple grape juice (PGJ), a natural carbohydrate- and polyphenol-rich supplement, may enhance exercise performance. This study, incorporating individual response analysis, examined the acute effects of PGJ ingestion on endurance, explosive power, and perceived fatigue in elite male soccer players.MethodologyTwenty-two U-20 male soccer players [Age: 19.7 ± 0.3; height: 178 ± 4 cm; body mass: 72 ± 5 kg; body mass index (BMI): 22.6 ± 0.9 kg/m2] participated in an equally allocated, double-blind, crossover design study. Participants were allocated to one of two conditions: (1) purple grape juice (PGJ, n = 11) or (2) placebo (PLA, n = 11). The PGJ or placebo was ingested in four equal portions (10 ml/kg of body mass PGJ or PLA diluted with water) starting 4 h before the test and continuing every hour, with the final ingestion 60 min before the 30-15 Intermittent Fitness Test (IFT). The placebo consisted of a calorie-free, grape-flavored liquid designed to match the taste and appearance of the PGJ. A 7 days washout period was maintained between the two conditions. Perceived fatigue and standing long jump (SLJ) performance were assessed at baseline, immediately and 5 min after the IFT. Maximum oxygen consumption (VO2max), time to exhaustion (TTE), and final velocity in the IFT (VIFT) were recorded during the test. The smallest worthwhile change (SWC) analysis was used to evaluate individual responses.ResultsPurple grape juice improved VIFT (P < 0.001, Cohen’s d = 0.58), TTE (P < 0.001, Cohen’s d = 0.69), and VO2max (P < 0.001, Cohen’s d = 0.56) compared to PLA. No effects were found for SLJ or perceived fatigue (P > 0.05), SWC analysis revealed that 77% of participants showed improvements in VIFT and VO2max, and 54% showed improvements in SLJ 5 min post-IFT.ConclusionPurple grape juice supplementation enhanced endurance performance parameters in most participants, with significant individual variability in response. These findings highlight the potential benefits of PGJ, particularly for athletes more responsive to its effects, emphasizing the need for personalized supplementation strategies.